Language practice and language ideology on linguistic landscape in Malaysia - Soon, Chiow Thai; Loi, Chek Kim; Ku Chen Jung @ Nur Alliyah Ku (Academia Industry Networks, 2021)
This paper explores the language choice in the business field through linguistic landscape in a multilingual community in a Federal Territory in Malaysia. The main aim of this paper is to examine the impact of language management (language policy) on the language practice (language use) and the language ideology (language belief) of a language community by using Spolsky’s theory of language management (2009). This ethnographic research also employs Ben-Rafael’s (2009) linguistic landscape to examine the language use and language beliefs reflected in the naming of companies. The corpora comprise 212 and 233 brand names collected in 2012 and 2018 respectively. They were analysed qualitatively to examine the patterns of language use. Interview sessions with seven company owners in the language community were conducted to explore their language ideology towards their language/s use on branding. The findings of this study show i) the use of Malay language for the company signs has higher frequency in the 2018’s data compared to the 2012’s data. (ii) the language community on the island supports the language policy implemented by the local authority because the status of Malay language is indisputable. The study suggests the existing signs should be preserved because they have historical heritage value and reflect the multilingual practice of the language community. In order to avoid making signboards that defy the language policy, new signboards submitted for approval should abide to the standard operation procedure set by the local authorities.